Books, bones and bodies: The relevance of the history of anatomy in Nazi Germany for medical education today. Issue 4 (12th June 2021) - Hildebrandt, Sabine
Abstract: The history of anatomy in Nazi Germany highlights the consequences to humanity when the destructive potentials immanent to all science and medicine are enabled by an anti‐democratic, totalitarian regime. Anatomy presents an example of ethical transgressions by scientists and health care professionals that were amplified in the criminal political climate of the Nazi regime. This can happen anywhere, as science is never apolitical. This article gives a short account of anatomy in Nazi Germany, which is followed by an outline of the tangible and intangible legacies from this history, to then discuss implications for anatomy education today. While Jewish and politically dissident anatomists were forced out of their positions and country by the Nazi regime, the majority of the remaining anatomists joined the Nazi party and used bodies of Nazi victims for education and research. Some anatomists even performed deadly human experiments. Patterns and legacies that emerge from this history can be traced into the present and concern research ethics in general and anatomical body procurement specifically. They shed light on current practices and controversies in the anatomical sciences, including anthropology. It will be argued here that the history of anatomy in Nazi Germany can inform current anatomy education in a concept of anatomy as the first "clinical discipline." By integrating insights from the history of anatomy into the learning process, anatomy education can model an approach to medicine that includes a full appreciation of the shared humanity of medical practitioners and patients.